2020
DOI: 10.1080/09297049.2020.1769582
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior during toddlerhood: Interrelated effects of prenatal risk factors, negative affect, and cognition

Abstract: Prenatal risk, temperamental negative affect, and specific cognitive abilities have all individually been identified as predictors of behavior problems during early childhood, but less is known about their interplay in relation to aggression during toddlerhood. This study examined the main and interaction effects of prenatal risk, negative affect, inhibitory control, attention, and vocabulary in the prediction of aggression in 150 children (75 boys). During pregnancy, a cumulative risk index was calculated bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…In line with existing literature, child, mother, and household demographic risks all had direct and indirect effects for increased conduct problems over the course of development (from 3 to 17 years) [22,[25][26][27]. However and surprisingly, the mother and household risks were found to play no direct role in promoting head injuries during childhood (from age 9 months).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In line with existing literature, child, mother, and household demographic risks all had direct and indirect effects for increased conduct problems over the course of development (from 3 to 17 years) [22,[25][26][27]. However and surprisingly, the mother and household risks were found to play no direct role in promoting head injuries during childhood (from age 9 months).…”
Section: Discussionsupporting
confidence: 74%
“…Child level risk factors were taken from the parent interview at T1 and included male sex [2,22], low birth weight (<2.5 kg) and premature birth (<=252 days gestation) [23,24], and (due to biological effects on the child) whether the child’s biological mother smoked or drank alcohol during pregnancy [25,26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That our models selected no CpGs overlapping with these studies was unsurprising, since it was previously shown that the top CpGs from these studies were not associated with aggressive behavior in the buccal DNA methylation data in the NTR and LUMC-Curium cohorts (van Dongen et al 2021 ). Trait enrichment of the CpGs selected by the single- and multi-omics models reported enrichment of known aggression risk factors, such as socioeconomic status (Miller and Tolan 2019 ; Bellair et al 2019 ; Hendriks et al 2020 ), childhood malnutrition (Liu 2004 ; Vaughn et al 2016 ), and pre- and perinatal risk factors (Van Adrichem et al 2020 ). Moreover, we observed trait enrichment for several syndromes, e.g., Down syndrome, that are characterized by intellectual disability, developmental delay, and sometimes by aggressive behaviors among affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…That our models selected no CpGs overlapping with these studies was unsurprising, since it was previously shown that the top CpGs from these studies were not associated with aggressive behavior in the buccal DNA methylation data in the NTR and LUMC-Curium cohorts (van Dongen et al 2021). Trait enrichment of the CpGs selected by the single- and multi-omics models reported enrichment of known aggression risk factors, such as socioeconomic status (Miller and Tolan 2019; Bellair et al 2019; Hendriks et al 2020), childhood malnutrition (Liu 2004; Vaughn et al 2016), and pre-and perinatal risk factors (Van Adrichem et al 2020). Moreover, we observed trait enrichment for several syndromes, e.g., Down syndrome, that are characterized by intellectual disability, developmental delay, and sometimes by aggressive behaviors among affected individuals.…”
Section: Discussionmentioning
confidence: 99%